Effects of financial management practices on technical performance of building contractors in northeast Nigeria. Issue 2 (28th April 2020) - Sa'eed, Abdulmalik; Gambo, Nuru; Inuwa, Ibrahim Ibrahim; Musonda, Innocent
Abstract : Purpose: The purpose of this study is to assess the effects of financial management practices of small-scale building contractors on the technical performance of the contractors in the northern part of Nigeria with international best practices. Previous studies argued that the technical performance of small-scale building contractors in developing countries is poor because of insufficient cash to acquire strategic resources at the outset of a project. This continues to pose a challenge to the sustainable development of the construction industry, particularly in developing countries like Nigeria. There is, therefore, a need to identify, assess and compare the effects of financial practices of the contractors with technical performance best practices. Design/methodology/approach: The technical performance of each contractor was evaluated using a five-point Likert scale. This is used to obtain the mean technical performance levels of the contractors. A questionnaire survey was administered to the professionals in the industry who were selected by using a proportionate stratified random sampling technique. The contractors' performance was compared using ANOVA with post hoc, and the effects of contractors' financial management practices were determined using multiple regression analysis. Findings: The results of this study indicated that the contractors in Nigeria were average technical performers and there were large effects of financial management practices on the technical performance of contractors in building projects. Research limitations/implications: This study is limited to small-scale building contractors in northeast Nigeria. One of the implications of this study is that it provides the criteria for an evaluation of small-scale building contractors' technical performance in Nigeria and other developing countries that faced similar problems. Practical implications: The practical implications of this study are that it establishes the current level of contractors' technical performance and serves as an awareness of contractors' current financial practices. Social implications: This study created bases for self-evaluation of contractors' technical performance and competition among small-scale contractors in Nigeria for the enhancement of productivity particularly in rural areas for national development. Originality/value: This study emanated from the government reports and past studies in the area of performance management based on the persistence of poor technical performance of small-scale contractors in the construction industry.